a) \(\dfrac{3}{2}-\left|2x-\dfrac{2}{3}\right|=-\dfrac{5}{6}\)
\(\Leftrightarrow\left|2x-\dfrac{2}{3}\right|=\dfrac{3}{2}-\left(-\dfrac{5}{6}\right)=\dfrac{7}{3}\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-\dfrac{2}{3}=\dfrac{7}{3}\\2x-\dfrac{2}{3}=\dfrac{-7}{3}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3}{2}\\-\dfrac{5}{6}\end{matrix}\right.\)
b)\(\dfrac{2}{1}.\left|2x-\dfrac{1}{3}\right|-\dfrac{3}{2}=\dfrac{1}{4}\)
\(\Leftrightarrow2\left|2x-\dfrac{1}{3}\right|=\dfrac{1}{4}+\dfrac{3}{2}=\dfrac{7}{4}\)
\(\Leftrightarrow\left|2x-\dfrac{1}{3}\right|=\dfrac{7}{4}:2=\dfrac{7}{8}\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-\dfrac{1}{3}=\dfrac{7}{8}\\2x-\dfrac{1}{3}=-\dfrac{7}{8}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{29}{48}\\x=-\dfrac{13}{48}\end{matrix}\right.\)